Influence of Perceived Ease and Usefulness on the Acceptance of AI Features in Mobile Banking: Evidence from Palopo City, Indonesia - Winanda Winanda; Antong Antong; Goso Goso (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study examines the influence of perceived ease of use and perceived usefulness on the acceptance of Artificial Intelligence (AI) features in mobile banking among Generation Z users in Palopo City, Indonesia. The research addresses the growing need to understand user acceptance of AI-driven financial services in regional contexts. Methodology: A quantitative approach was employed using an online survey distributed to 210 mobile banking users selected through purposive sampling. Data were analyzed using multiple linear regression to assess both partial and simultaneous effects of the independent variables on AI feature acceptance. Results: The findings indicate that perceived ease of use and perceived usefulness have significant positive effects on the acceptance of AI features in mobile banking. Perceived usefulness exerts a stronger influence than perceived ease of use. The model explains 60.5% of the variance in AI feature acceptance. Findings: The results confirm the relevance of the Technology Acceptance Model (TAM) in explaining AI adoption in mobile banking. Novelty & Originality: This study offers novelty by focusing on Generation Z users in Palopo City, a regional context rarely examined in prior research on AI-based fintech acceptance. Conclusions: The study provides theoretical support for TAM and offers practical implications for banking institutions to enhance AI feature adoption by improving usability and emphasizing functional benefits. Type of Paper: This paper is an empirical research paper.